Agapetes brevipedicellata (Ericaceae), a new species from Putao, Kachin State, Northern Myanmar - Zhou, Shi-Shun; Yang, Bin; Tong, Yi-Hua; Ding, Hong-Bo; Li, Ren; Kyaw, Win Maung; Tan, Yun-Hong (Phytotaxa, 2017)
Agapetes brevipedicellata, a new species of Ericaceae from Putao, Kachin State, Myanmar, is here described and illustrated. It is morphologically similar to Agapetes pseudogriffithii, but can be easily distinguished from the latter by its nearly fleshy branchlets, linear-lanceolate leaf blades, stout, fleshy, bracteate peduncles, pedicels and calyx pale greenish tinged with pale pink, and stems and branches with prominent leaf and inflorescence scars.